The association between motor capacity and motor performance in school-aged children with cerebral palsy: An observational study - Min-Hwa Suk; In-Kyeong Park; Soojin Yoo; Jeong-Yi Kwon (Elsevier, 2021)
Background: This study aimed to investigate the association between motor capacity and motor performance in children with cerebral palsy (CP) aged 6-12 years with Gross Motor Function Classification System (GMFCS) levels I to III. Methods: Forty-six children with CP (24 boys and 22 girls) classified as GMFCS levels Ⅰ, Ⅱ, or Ⅲ were included. Motor capacity was measured by the Gross motor function measure (GMFM), Pediatric balance scale (PBS), Timed up and go (TUG), and 6-min walk test (6MWT). Motor performance was measured by triaxial accelerometers. Estimations of physical activity energy expenditure (PAEE) (kcal/kg/day), percentage of time spent on physical activity (% sedentary physical activity; %SPA; % light physical activity, %LPA; % moderate physical activity, %MPA; % vigorous physical activity %VPA; and moderate-to-vigorous physical activity, %MVPA), and activity counts (counts/minute) were obtained. Results: Children with GMFCS level I showed a significantly higher motor capacity (GMFM-66, GMFM-88, D-dimension and E-dimension, PBS and 6MWT) than those with level II or III. Children with GMFCS level II and/or III had significantly lower physical activity (PAEE, % MPA, % VPA, %MVPA, and activity counts) than children with GMFCS level I. Multiple linear regression analysis (dependent variable, GMFM-66) showed that %MVPA was positively associated with GMFM-66 in the GMFCS level II & III children but not in GMFCS level I children. Conclusions: These findings highlight the importance of increasing %MVPA in children with CP, especially GMFCS levels II and III.